On the role of cortical area V4 in the discrimination of hue and pattern in macaque monkeys. - Heywood, C; Cowey, A (1987)
Cortical visual area V4 in macaque monkeys has a large proportion of neurons that are sensitive to the wavelength or to the color of light. We tested its role in hue discrimination by removing it in macaque monkeys trained to discriminate small differences in hue. Hue discrimination thresholds were permanently elevated in 4 macaque monkeys in which V4 was removed bilaterally. In contrast, there was no impairment in achromatic intensity thresholds tested in an identical manner. However, the discrimination of pattern and orientation was also conspicuously impaired, indicating that area V4 is not concerned solely with processing information about wavelength. The multiple defect is consistent with evidence that V4 provides the major cortical visual input to the temporal lobe, where a large range of visual properties is registered. The performance of monkeys with V4 ablation was compared with that of unoperated control monkeys and monkeys with removal of cortex in the banks and floor of the rostral superior temporal sulcus (STS). Removal of STS had only slight effects on pattern discrimination and none of hue discrimination. To control for the possible effects of inadvertent damage to the visual radiations when removing V4, the lateral striate cortex was partially ablated bilaterally in a control monkey. This had no effect on any discrimination, despite producing more retrograde damage to the lateral geniculate nuclei than in any monkey with V4 ablation. The visual disorder following removal of visual area V4 strikingly resembles the clinical disorder of mild cerebral achromatopsia with associated apperceptive agnosia for objects and patterns.